2022
DOI: 10.1186/s13006-022-00519-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between exclusive breastfeeding and postpartum post-traumatic stress disorder

Abstract: Background Research on the association between breastfeeding and postpartum post-traumatic stress disorder (PTSD) is sparse. This study aimed to examine the association between exclusive breastfeeding up to 42 days after childbirth and postpartum PTSD. Methods An epidemiologic study was conducted in a tertiary hospital in China between October 2019 and October 2020. Eligible mothers were recruited at 3 days after childbirth and assessed using the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Additionally, a significant negative correlation was observed between PTSD score and BAES. Consistent with our study, İsbir et al reported that antenatal education was associated with a reduced incidence of postpartum PTSD [23]. These results emphasize the importance of prenatal education about breastfeeding for all pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a significant negative correlation was observed between PTSD score and BAES. Consistent with our study, İsbir et al reported that antenatal education was associated with a reduced incidence of postpartum PTSD [23]. These results emphasize the importance of prenatal education about breastfeeding for all pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…A significant protective role in the risk for postpartum PTSD appeared to be played by the partner ( 35 ) , as well as direct breastfeeding within the first hour ( 36 ). Regarding the support of the husband, it seems certain that it acts as a protective factor for the appearance of anxiety, stress, and depression.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of intrinsic motivation for prolonged breastfeeding, based on life experiences related to the prenatal and postpartum period, has been described (Martínez-Poblete & Ossa, 2020). According to Chen et al (2022), the post-traumatic stress from-and negative experiences with-childbirth negatively influence the establishment and maintenance of breastfeeding practices. However, an innovative finding in the present study is that the participants alleviated the pain and frustration they associated with their traumatic childbirth with the establishment of a bond with their child(ren).…”
Section: Discussionmentioning
confidence: 99%